DIGITAL WALLET ADOPTION FOR REPEAT INFAQ PAYMENT: INTEGRATING RELIGIOSITY – INTENTION MODEL - Purbasari, Lintang Titian; Tri Ratnasari, Ririn; Ab Rahman, Asmak (Jurnal Syariah, 2023)
This paper aims to investigate the integration of the TAM model and the religious intention model in the adoption of a digital wallet for sustainable infaq payments. The information was gathered through an online survey of 100 members of Gen-Z in Indonesia who use digital wallets and have made infaq payments using digital wallets. The relationship between religiosity, perceived ease of use, satisfaction, attitude, and intention to pay recurrent infaq is assessed using a quantitative approach and SEM techniques via smart-PLS. The results of the study show that the religious-intention integration model provides a more complete explanation regarding the adoption of digital wallets for recurring infaq payments. Apart from perceived ease of use, satisfaction, and attitudes, this research also focuses on how important religiosity is for digital wallet adoption. This research can be used by the government to increase the adoption of digital wallet services in Gen-Z and create a culture in the future to donate through digital wallets because their trust and feel it is easy to use. All marketing strategies must focus on providing high-quality digital wallet services and ensuring digital wallets comply with Islamic law so that Gen-Z is more aware of infaq through digital wallets.